Functional range of motion of the elbow - Vasen, A P; Lacey, S H; Keith, M W; Shaffer, J W (The Journal of hand surgery (American ed.), 1995)
One hundred normal upper extremities in 50 adults were sequentially studied in a Bledsoe brace, which limited elbow motion. The amount of flexion and extension of the elbow was serially limited by 15 degree increments. At each setting, the subjects were asked to perform 12 activities of daily living. The percentage of subjects who completed each task with the specified range of motion was determined. Overall, 49 of the subjects performed all of the tasks with extension limited at 75 degrees and flexion limited at 120 degrees. By isolating the allowable range of motion of the elbow and allowing for compensatory motions and strategies of the normal adjacent joints, the functional elbow range of motion is established as 75 degrees-120 degrees flexion. Thus, the functional status of a patient with a specific elbow range of motion can be predicted more accurately.